Development of a cartesian board learning media to enhance students’ problem-solving in translation and reflection - Nurul Ilmi Badrud Dhujjah; Abd. Qohar; Hery Susanto; Puguh Darmawan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Learning geometric transformation, particularly translation and reflection, often relies heavily on symbolic explanations, leading to students' difficulties in spatial visualization and problem-solving. While mathematics manipulatives provide concrete interactions to bridge abstract concepts, their specific development for transformation geometry remains limited.Aims: This study aims to develop a Cartesian board learning media and evaluate its validity, practicality, and effectiveness in enhancing Grade IX students' problem-solving abilities in translation and reflection.Method: This study employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects were Grade IX students. Data were collected using expert validation sheets, student response questionnaires, classroom observation sheets, and problem-solving tests (pretest and posttest).Results: Expert validation results indicated that the Cartesian board learning media is highly valid with an average score of 3.70. The media also proved to be highly practical, achieving an average score of 3.59 based on positive student responses and classroom observations. Furthermore, the media effectively improved students' problem-solving skills, as evidenced by the increase in the average test score from 61.30 to 79.78, yielding a moderate N-Gain score of 0.53.Conclusion: The developed Cartesian board is a valid, practical, and effective learning manipulative that significantly enhances students' problem-solving abilities in geometric transformation.